BUDAYA TERTIB BERLALU-LINTAS: Kajian Fenomenologis atas Masyarakat Pengendara Sepeda Motor di Kota Bandung - Soni Sadono (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2015)
The weak of public awareness of traffic regulation seen from low level of the discipline in driving, that produce undisciplined culture to the society. Lacking awareness from people in traffic rules can be seen in behavior like an increased by offense traffic motorists. This was found in many offense of the traffic signs in Bandung in 2014 by the number of 39.205 offense (Source : Polwiltabes Bandung, 2015). Undisciplined behaviour of people in traffic as driving exceeds the speed limit determined, passing traffic lights, passing marka roadblock, no complete safety equipment as well not use helmet, informer to, vehicles lights, incompleteness motor vehicles letter, disobedient pay taxes, and could not be used vehicles. A traffic violation often happens also involved in â€œa rider breaking the traffic congestion, driving zigzag at high speed, and even had breaking the traffic lights, and breaking the banned curvyâ€ (Hendratno, 2009 :499). This journal trying to elaborate on literature and field research of the problems of culture orderly traffic, with a qualitative approach.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords : culture, traffics, discipline attitude, phenomenologyThe weak of public awareness of traffic regulation seen from low level of the discipline indriving, that produce undisciplined culture to the society. Lacking awareness from people intraffic rules can be seen in behavior like an increased by offense traffic motorists. This wasfound in many offense of the traffic signs in Bandung in 2014 by the number of 39.205 offense(Source : Polwiltabes Bandung, 2015). Undisciplined behaviour of people in traffic as drivingexceeds the speed limit determined, passing traffic lights, passing marka roadblock, no completesafety equipment as well not use helmet, informer to, vehicles lights, incompleteness motorvehicles letter, disobedient pay taxes, and could not be used vehicles. A traffic violation oftenhappens also involved in â€œa rider breaking the traffic congestion, driving zigzag at high speed,and even had breaking the traffic lights, and breaking the banned curvyâ€ (Hendratno, 2009 :499). This journal trying to elaborate on literature and field research of the problems of cultureorderly traffic, with a qualitative approach.Keywords : culture, traffics, discipline attitude, phenomenology